2015
DOI: 10.1002/2015ja021069
|View full text |Cite
|
Sign up to set email alerts
|

The 4 June 2011 neutron event at Mercury: A defense of the solar origin hypothesis

Abstract: We address the claim that an increase in the flux of neutrons detected by the Neutron Spectrometer (NS) on the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft in orbit about Mercury at 15:45 UTC on 4 June 2011 was generated by the impact of energetic ions onto spacecraft. We find this claim to be unwarranted. The claim is grounded on the erroneous assumption that the NS singles count rate is triggered only by energetic ions. Rather, because any mix of energetic ions, electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Based on instrument modeling, this triple-coincidence count rate measures the integral flux of protons and alpha particles greater than 125 MeV/nucleon and thus serves as a proxy for GCR flux for the vicinity around the MESSENGER spacecraft. To date, energetic particle data from the NS have been used to make corrections to neutron data measured during the first year of orbital operations [Lawrence et al, 2013] and to understand the interaction of charged particles with the MESSENGER spacecraft for studies of solar neutrons Lawrence et al, 2014Lawrence et al, , 2015. In addition, Rodgers et al [2015] reported GCR variations in the inner heliosphere for distances ranging from 0.3 to 0.85 AU based on NS measurements from the MESSENGER cruise phase that lasted from 2004 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Based on instrument modeling, this triple-coincidence count rate measures the integral flux of protons and alpha particles greater than 125 MeV/nucleon and thus serves as a proxy for GCR flux for the vicinity around the MESSENGER spacecraft. To date, energetic particle data from the NS have been used to make corrections to neutron data measured during the first year of orbital operations [Lawrence et al, 2013] and to understand the interaction of charged particles with the MESSENGER spacecraft for studies of solar neutrons Lawrence et al, 2014Lawrence et al, , 2015. In addition, Rodgers et al [2015] reported GCR variations in the inner heliosphere for distances ranging from 0.3 to 0.85 AU based on NS measurements from the MESSENGER cruise phase that lasted from 2004 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…[] and later defended in Lawrence et al . []. However, we also note that the count rate of fast neutrons between 0.5 and 8 MeV registered by the MESSENGER NS in response to these normalized H and He spectra incident on MESSENGER spacecraft material should be proportional to the LG2dbl count rate if the neutrons are generated locally by the energetic ion environment at MESSENGER.…”
Section: Observations At Messengermentioning
confidence: 79%
“…This fact drove our conclusion that the neutrons observed in this event could not have been produced on the spacecraft by local energetic particles. This conclusion is strengthened by the absence of detection of an enhancement of a Mg(p,γ) line at 1635 keV by the MESSENGER GRS [see also Lawrence et al ., ].…”
Section: Observations At Messengermentioning
confidence: 99%
See 2 more Smart Citations